Mitigation of N2O emissions from grassland by nitrification inhibitor and actilith F2 applied with fertilizer and cattle slurry - Merino, P.; Estavillo, J. M.; Graciolli, L. A. [UNESP]; Pinto, M.; Lacuesta, M.; Muñoz-Rueda, A.; Gonzalez-Murua, C. (Wiley, 2002)
Nitrous oxide (N2O) is involved in both ozone destruction and global warming. In agricultural soils it is produced by nitrification and denitrification mainly after fertilization. Nitrification inhibitors have been proposed as one of the management tools for the reduction of the potential hazards of fertilizer-derived N2O. Addition of nitrification inhibitors to fertilizers maintains soil N in ammonium form, thereby gaseous N losses by nitrification and denitrification are less likely to occur and there is increased N utilization by the sward. We present a study aimed to evaluate the effectiveness of the nitrification inhibitor dicyandiamide (DCD) and of the slurry additive Actilith F2 on N2O emissions following application of calcium ammonium nitrate or cattle slurry to a mixed clover/ryegrass sward in the Basque Country. The results indicate that large differences in N2O emission occur depending on fertilizer type and the presence or absence of a nitrification inhibitor. There is considerable scope for immediate reduction of emissions by applying DCD with calcium ammonium nitrate or cattle slurry. DCD, applied at 25 kg ha-1, reduced the amount of N lost as N2O by 60% and 42% when applied with cattle slurry and calcium ammonium nitrate, respectively. Actilith F2 did not reduce N2O emissions and it produced a long lasting mineralization of previously immobilized added N.
Keywords: Cattle slurry; Emissions; Grasslands; Nitrification inhibitors; Nitrogen fertilizers; Nitrous oxide; fertilizer application; grassland; nitrous oxide; slurry; Spain; Bos taurus; Lolium; Trifolium